Media framing of peace and war news: a comparative study between Malaysian TV stations and the global media / Faridah Ibrahim - Ibrahim, Faridah (CMIWS and UiTM Press, 2010)
In the 1990s we witnessed wars via the mass media; death of thousands in several warring states and millions in others. We also witnessed numerous acts of terrorism for instance 9/11 in America, the 7/7 bomb blast in the British capital and several bomb blast in Malaysian neighboring country, Indonesia. In the midst of these happenings, are the media, both local and global, doing their best to cover the news for the benefits of their audiences locally or worldwide. As for the local media, and in this case the news broadcast, one may ask how does a country such as Malaysia, that does not experience war, report other peoples' war? With Malaysia's over dependence of war news from the international news agencies and global media, will the news by Malaysian broadcast media differ from those that are covered by the global media, due to news slant and editors' preferences? Moreover with the potential of the mass media to provide neutral and objective reporting of war and peace, one may ask, how do these local and global media propagate peace? For that matter, is peace journalism an option for these media. This study engages in a comparative study on the coverage of war and peace news between two Malaysian television stations, TV3 and RTM with two global television networks, CNN and Al-Jazeera. Using a quantitative content analysis study with Smetko and Valkenburg's framing theory as the theoretical platform, the study hopes to identify to what extent these four selected media are involved in propagating world peace.